Some considerations on urban life style - Barreto, Maria Amália Pereira (Universidade Estadual Paulista / UNESP, 2009)
This paper consistis in some reflexions about terms like urban, life style, style. authors consulted were Simmel, Park, Redfield and Wirth and Wirth by one way and Schütz, Berger Suckmann by another.